THE ROLE OF ARTIFICIAL INTELLIGENCE (AI) IN IMPROVING THE ACCURACY OF FUTURE COST MEASUREMENT AND COST DESIGN - TOWARDS A PROACTIVE COST SYSTEM THAT SUPPORTS STRATEGIC DECISIONS: AN APPLIED STUDY IN OR GENERAL ENGINEERING INDUSTRIES COMPANY - Ali Abdul-Hussein Hani Al-Zameli (Scholar Express Journals, 2026)
This research is a first step to investigate how artificial intelligence could facilitate next cost estimation and cost planning to design a proactive cost system which supports decision makers at the strategic level. The study was conducted under real factory conditions and involved a case study at OR General Engineering Industry; it was based on real accounting and cost information, and utilized artificial intelligence (AI) models and techniques including neural networks, and machine learning. The paper contributes on tackling the limitations of traditional cost systems which do not allow the prediction of future costs nor the design of the product cost considering the strategic directions of the organization. A knowledge-based cost model was developed using the real past company data and operational data, showing the potential of increasing the accuracy of cost predicting and to support decisions on pricing, planning and production. The study reveals that the application of AI to the cost system is really beneficial, since it not only increases the accuracy of information, but also helps users to make better decisions and attain competitiveness in the industrial business market.And, this study implies significant need that industrial firms should attain this technological orientation and develop digital infrastructures that enable it.
Keywords: Artificial Intelligence; Future Cost Measurement; Cost Design